2021
DOI: 10.1007/s10695-021-00950-9
|View full text |Cite
|
Sign up to set email alerts
|

RM12 similar to substance P from tachykinin of freshwater murrel Channa striatus influence intracellular ROS in vitro fish erythrocytes and developmental toxicity and antioxidant enzymes in vivo zebrafish embryo

Abstract: zebrafish embryo, the intracellular ROS level was estimated by 5 mM H 2 O 2 stress in the zebrafish embryo, and inhibition of apoptosis was evaluated. The antioxidant enzymes were extracted from the H 2 O 2 -stressed zebrafish embryo, and the intracellular ROS was eliminated due to RM12. Collectively, the experiment showed that the substance P from the freshwater murrel C. striatus possessed potent antioxidant properties; thus, it can further be focused to develop it as antioxidant molecule in aquaculture orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Somite should be formed at least at 48 hpf, failing which the embryo was considered dead. Mortality was recorded till 96 hpf ( t = 24, 48, 72, and 96 hpf, n = 40/group, three independent experiments) 42 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Somite should be formed at least at 48 hpf, failing which the embryo was considered dead. Mortality was recorded till 96 hpf ( t = 24, 48, 72, and 96 hpf, n = 40/group, three independent experiments) 42 …”
Section: Methodsmentioning
confidence: 99%
“…Mortality was recorded till 96 hpf (t = 24, 48, 72, and 96 hpf, n = 40/group, three independent experiments). 42…”
Section: Mortalitymentioning
confidence: 99%
“…Approximately 20 articles from Google Scholar and 15 articles from PubMed were deemed relevant to our investigation. Notably, the most frequently cited papers included one by [14] with 28 citations, highlighting the disruption of zebrafish larval microbiomes and increased mortality induced by Streptomycin exposure. Another study by [15], with 6 citations, reported elevated mortality and skeletal deformities in zebrafish exposed to MS-222 during early development.…”
Section: Introductionmentioning
confidence: 99%